Preparação física, prevenção e tratamento de lesões em praticantes de Rugby com o Método Pilates: revisão da literatura - Inforzato, Italo José (2022)
Rugby is a team sport of sprints and intense physical contact where players engage in physical disputes all the time, thus, the sport requires a high level of endurance, strategy and skills from its athletes, to reach the desired level of performance during the matches, athletes have to develop to the maximum physical and motor skills like: strength, endurance, speed, motor coordination, joint mobility and flexibility. Rugby players, like in the other sports, are susceptible to injuries, one of the measures to avoid or treat them is flexibility training and joint mobility protocols. The Pilates method was initially created as a practice that mixed elements of gymnastics, martial arts and dance, always focusing on the relationship between body and mind. Recently, the traditional elements of the Pilates method have evolved, also incorporating rehabilitation and physical conditioning, where the focus of these elements is to return the functional activities providing the necessary assistence and training, as well as improving the efficiency of movements and physical conditioning. The exercises of the Pilates method bring precisely this proposal, through the strengthening, they improve posture and breathing coordination, leading to a general improvement in flexibility and joint mobility. A bibliographic review was made looking for studies where the Pilates method was used as a tool to increase flexibility, joint mobility and also as a training tool to increase the physical conditioning of rugby players.